Causality Assessment of Cutaneous Adverse Drug Reactions - Son, Young-Min (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2011)
BACKGROUND: Cutaneous adverse drug reactions (ADRs) are the most common adverse reactions attributed to drugs. A systematic and effective approach to a patient with suspected drug eruption allows for prompt recognition, classification and treatment of cutaneous ADRs. A standardized and effective approach for objective causality assessment is necessary to make consistent and accurate identification of ADRs. OBJECTIVE: Although the Naranjo algorithm is the most widely used assessment tool, it contains many components which are not suitable for clinical assessment of ADRs in Korea. The purpose of this study is to compare correlations of the Naranjo algorithm and the Korean algorithm to evaluate usefulness of both algorithms in order to make a causal link between drugs and cutaneous ADRs. In addition, this study classifies the clinical types and causative agents of cutaneous ADRs. METHODS: The authors retrospectively reviewed the clinical types and laboratory findings of patients who were diagnosed with cutaneous ADRs in the dermatology clinic at Gil hospital. One hundred forty-one patients were enrolled in this evaluation. The causal relationship of ADRs was assessed by using the Naranjo algorithm and Korean algorithm (version 2.0). RESULTS: A cross-tabulation analysis was applied to the Naranjo algorithm and Korean algorithm (version 2.0). Simple correlation analysis and a Bland-Altman plot were used for statistical analysis. Correlation analysis confirmed that the two assessment algorithms were significantly correlated. Exanthematous eruptions (68.8%), Stevens- Johnson syndrome (10.6%), and urticaria (8.5%) were the most common types of cutaneoues ADRs. The most common causative agents were antibiotics/antimicrobials, antipyretics/non-steroidal anti-inflammatory drugs, and central nervous system depressants. CONCLUSION: The Naranjo algorithm and Korean algorithm (version 2.0) were significantly correlated with each other, and thus reliable assessment methods to determine cutaneous ADRs.